Increased Frequency of Immune Thrombocytopenic Purpura in Coeliac Disease and Vice Versa: A Prospective Observational Study. (23rd April 2018) - Bibbò, Stefano; Fozza, Claudio; Pes, Giovanni Mario; Rojas, Rodrigo; Manetti, Roberto; Dore, Maria Pina
Abstract : Introduction . Coeliac disease (CD) and immune thrombocytopenic purpura (ITP) are immune conditions, often associated with other immune disorders. In recent years, increasing attention has been directed towards the association between ITP and CD. Aim . To investigate the frequency of ITP in CD patients and vice versa and to assess the risk of their association. Patients and Methods . This was a prospective observational study. All consecutive patients with CD or ITP attending our department were enrolled between January 2016 and December 2017. All patients with CD were screened for ITP and patients with ITP for CD. Odds ratios (ORs) were calculated based on the prevalence in the general population. Results . Two hundred sixty-one CD patients (212 female, mean age 47 ± 16.1 years) and 32 ITP patients (17 female, mean age 57.8 ± 17.4 years) were enrolled. In the CD cohort, two patients (2/261; 0.8%) reported a previous diagnosis of ITP, compared to the general population; OR was 15.3 (95% CI, 3.82–61.73; p < 0.0001 ). Similarly, in the ITP cohort, two patients (2/32; 6.3%) had a previous diagnosis of CD (OR: 9.89, 95% CI, 2.27–43.16; p = 0.0002 ). Discussion . A greater frequency of ITP in coeliac patients and vice versa was observed in our study, suggesting an increased risk for patients of developing both disorders.